AN ANALYSIS OF STUDENTS’ PERCEPTION USING KAHOOT GAME IN VOCABULARY LEARNING PROCESS - Nirwana Darwis; Nur Ikhsan Amal (Institut Agama Islam Negeri (IAIN) Bone, 2023)
In general, teaching and learning activities are mostly supported by books, the presentation of the materials by the teacher, and written or oral exercises. This type of learning method is monotonous. With technological developments and the internet as an educator, it is reasonable to utilize technology-based online learning applications, such as Kahoot. This research aims to find out the students' perceptions using Kahoot game in the vocabulary learning process. The participants of this research are XI Bahasa class students at MAN 1 BONE who have experienced using Kahoot. This qualitative research used questionnaire, interview, and documentation as instruments, purposive sampling technique was used to select participants to get data through interview. The results showed that Kahoot provides many positive impacts on students' learning. It was found that students perceive Kahoot as an online learning platform that increases interest, improves their vocabulary knowledge, and increases their motivation and enthusiasm which leads to active learning through flexible learning process. In addition, this research found difficulties that students experienced when using Kahoot, such as poor internet connection.